Relational vulnerability in motherhood—an existential perspective on pain and exhaustion among women - Gebhardt, Anja J.; Andermo, Susanne; Arman, Maria (Frontiers in Psychology, 2024)
Stress-related ill-health like pain and exhaustion are demanding public health problems in Europe. In Sweden, women are particularly at risk to develop stress-related ill-health during a period in life that coincides with child-rearing years. When entering motherhood, Swedish women's sick leave substantially increases. Yet, motherhood is rarely acknowledged in clinical encounters concerning pain and exhaustion although women suffer from these ailments more often than men. To incorporate motherhood as an existential dimension of health in the care of women living with pain and exhaustion might alleviate women's suffering. But knowledge on women's experiences of motherhood and health is scarce. Therefore, the aim of the study is to reach a deeper understanding of how women suffering from long-lasting pain and exhaustion experience their health in relation to motherhood. Ricoeur's interpretation theory has been applied to analyze 27 phenomenological interviews with 14 mothers suffering from long-lasting pain and exhaustion. These women's experiences shed light on how closely motherhood is interwoven with the experience of their health and suffering: The women's suffering seems to be rooted in a relational vulnerability that has been uncovered during motherhood. Further, the women suffer from a burden of difficult life experiences and inner conflicts. Reconciliation with life is possible when women find an existential shelter, which offers ways to relate to their suffering making the own suffering more bearable.